If f : R → R satisfies f ( x + f ( y ) − 1 ) = y + f ( x ) , then what is f ( 0 ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
f is not necessarily a polynomial; apart from that good solution.
Log in to reply
Yes, you are right. I failed to see that.
It is a polynomial function of type f ( x ) = x + 1
@Wen Z , @Akash Shukla , I have provided another solution.
Log in to reply
Yes, I did it in the same way. But it can't be done by taking y=ax, a ∈ R
Sorry about this but there is also a mistake in this solution...
You can only let z=1 if there exists an x such that x + f ( x ) = 1 .
f
(
x
+
f
(
y
)
−
1
)
=
y
+
f
(
x
)
⋯
(
1
)
Put
x
=
1
,
f
(
f
(
y
)
)
=
y
+
f
(
1
)
⋯
(
2
)
Apply
f
on both sides of
(
1
)
and simplify with
(
2
)
,
f
(
f
(
x
+
f
(
y
)
−
1
)
)
=
f
(
y
+
f
(
x
)
)
x
+
f
(
y
)
−
1
+
f
(
1
)
=
f
(
y
+
f
(
x
)
)
Put
y
=
0
,
x
+
f
(
0
)
−
1
+
f
(
1
)
=
f
(
f
(
x
)
)
⋯
(
3
)
Compare
(
2
)
with
(
3
)
,
f
(
0
)
=
1
Put y = 0 and x = 1
f ( 1 + f ( 0 ) − 1 ) = 0 + f ( 1 )
⇒ f ( f ( 0 ) ) = f ( 1 )
Hence, f ( 0 ) = 1
Taking , x = 1 and y = 0 ,
we get , f ( 1 + f ( 0 ) − 1 ) = 0 + f ( 1 ) ,
( f ( f ( 0 ) ) ) = f ( 1 ) ⟹ f ( 0 ) = 1
You need to prove injectivity first; that is
f ( a ) = f ( b ) ⟹ a = b
Problem Loading...
Note Loading...
Set Loading...
f ( x + f ( y ) − 1 ) f ( x + f ( x ) − 1 ) f ( z − 1 ) f ( 0 ) = y + f ( x ) Let y = x = x + f ( x ) Let x + f ( x ) = z = z Let z = 1 = 1
Previous solution
Since y in the RHS of f ( x + f ( y ) − 1 ) = y + f ( x ) has a degree of 1, for the LHS = RHS for all x and y , the degree of f must be 1. So, we can assume f ( x ) = a x + b . Then we have:
f ( x + f ( y ) − 1 ) f ( x + a y + b − 1 ) a x + a 2 y + a b − a + b a 2 y + a b − a = y + f ( x ) = y + a x + b = a x + y + b = y
Equating the coefficients of y and the constant on both sides:
⟹ { a 2 = 1 a b − a = 0 ⟹ a = ± 1 ⟹ b = 1
⟹ f ( x ) f ( 0 ) = ± x + 1 = 1